2023
DOI: 10.1136/gutjnl-2022-328708
|View full text |Cite|
|
Sign up to set email alerts
|

Sympathetic nervous activation, mitochondrial dysfunction and outcome in acutely decompensated cirrhosis: the metabolomic prognostic models (CLIF-C MET)

Abstract: Background and aimsCurrent prognostic scores of patients with acutely decompensated cirrhosis (AD), particularly those with acute-on-chronic liver failure (ACLF), underestimate the risk of mortality. This is probably because systemic inflammation (SI), the major driver of AD/ACLF, is not reflected in the scores. SI induces metabolic changes, which impair delivery of the necessary energy for the immune reaction. This investigation aimed to identify metabolites associated with short-term (28-day) death and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Weiss et al showed in two prospective multicentre large cohorts from (CANONIC (discovery, n=831) and PREDICT (validation, n=851)) that models including metabolites (CLIF-C MET)—here the prognostic composite biomarker—reflecting SI, mitochondrial dysfunction and sympathetic system activation were superior to prognostic short-term mortality using established clinical scores (eg, MELDNa). 23 Such prognostic biomarkers are also used in clinical trials as a method to identify patients who might have a higher risk of developing the event of interest, and, as such, enable enrichment of trials and reduce sample size ( figure 1 ).…”
Section: Biomarker-guided Treatmentsmentioning
confidence: 99%
“…Weiss et al showed in two prospective multicentre large cohorts from (CANONIC (discovery, n=831) and PREDICT (validation, n=851)) that models including metabolites (CLIF-C MET)—here the prognostic composite biomarker—reflecting SI, mitochondrial dysfunction and sympathetic system activation were superior to prognostic short-term mortality using established clinical scores (eg, MELDNa). 23 Such prognostic biomarkers are also used in clinical trials as a method to identify patients who might have a higher risk of developing the event of interest, and, as such, enable enrichment of trials and reduce sample size ( figure 1 ).…”
Section: Biomarker-guided Treatmentsmentioning
confidence: 99%
“…Another recent publication by Weiss et al investigated the role of metabolites reflecting SI, mitochondrial dysfunction, and sympathetic system activation in predicting short term mortality in patients with ACLF, and invented the CLIF-C MET score. However, cost-effectiveness analysis and prospective validation of these markers and scores remains necessary [68].…”
Section: Lt In Ad and Aclfmentioning
confidence: 99%
“…On the other hand, patients with unstable decompensated cirrhosis (UDC), who will experience further decompensation without developing ACLF and have an intermediate risk of death, and patients with stable decompensated cirrhosis (SDC), who will not experience any further decompensation and have a lower risk of 1-year mortality. 3 Although our understanding of the pathophysiology of AD-ACLF syndrome has improved in the recent years, 4 leading to the "systemic inflammation hypothesis," 5 prediction of the individual patient's trajectory after AD remains challenging. 6,7 However, better identification of patients with AD at higher risk of progression would improve patient management (i.e., identification of candidates for an expedite evaluation for liver transplantation and/or disease-modifying therapies currently under investigation).…”
Section: Introductionmentioning
confidence: 99%
“…Although our understanding of the pathophysiology of AD‐ACLF syndrome has improved in the recent years, 4 leading to the “systemic inflammation hypothesis,” 5 prediction of the individual patient's trajectory after AD remains challenging 6,7 . However, better identification of patients with AD at higher risk of progression would improve patient management (i.e., identification of candidates for an expedite evaluation for liver transplantation and/or disease‐modifying therapies currently under investigation) 8–10 …”
Section: Introductionmentioning
confidence: 99%